Scope of territorial reconversion to mitigate conditioning factors of urban poverty - Quintana Noriega, Maria Carolina (2022)
This research work is a prospective exercise that identifies the location logics of urban facilities within the Zona Metropolitana del Valle de México (ZMVM) as a replicable methodology for Mexican cities. To this end, it is based on prospective scenarios, according to the Estructura del Sistema Normativo de Equipamiento Urbano (ESNEU) of the Secretaria de Desarrollo Social (SEDESOL, 1999) and on destinations of commercial, housing, industrial and agricultural land uses, which are integrated according to variables of social and economic capital, public or private property and population density, reflecting areas of population benefited and served to determine a logic of metropolitan location. By doing so, it analyzes the possible scope of territorial reconversion as an instrument of mitigation of certain socio-territorial factors, which condition urban poverty. At the same time, it recognizes a deficiency in access to education and health services in the urban peripheries, originated in market control and land ownership, real estate speculation and a logic in favor of private capital over the social welfare of lower income groups. It is in this sense that this study presents a model of the location logics of urban facilities inviting to review the current urban planning criteria, which operates on the territorial phenomena of the expansion of Mexican cities, in order to solve these particular problems of social backwardness, which affect the conditions of urban poverty.